The development of the Brazilian steel industry - Baer, Werner (Nashville, Tenn. : Vanderbilt University Press, 1969)
This provides a historical background of the cooperation between the public and private sectors of the Brazilian economy. It also examines the natural resources and the technology for the construction of the Brazilian steel mills. The book also analysed the impact of the industry on the Brazilian economy.
Includes index.
Includes bibliographical references: p. 183-186.
lje 21/01/2019
Loans
Keywords: Steel industry and trade; Economic growth; Brazil